2015
DOI: 10.3892/br.2015.528
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the influence on renal function between cefepime and cefpirome

Abstract: Abstract. Although known for their broad spectrum and curative efficacy on drug-resistant pathogens and as nephrotoxicity-free, impairments were observed on renal function during clinical treatment of the two most commonly used fourth-generation cephalosporins: Cefpirome and cefepime. The present study aimed to further explore the exact influences of them on renal function. In vitro, the cell viability of renal cells cultured in drug-combined medium was tested for six dilutions. In vivo, a clinical cohort stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 10 publications
0
7
0
3
Order By: Relevance
“…It is clinically applied in a various array of infections such as pneumonia as well as intra-abdominal, skin, urinary tract, and hospital-acquired infections. [5,6] Increasing evidence in preceding studies reported that CP therapy can cause renal insufficiency, [4] reproductive toxicity, [7] neurological disorder, and hepatic toxicity. [6,8] A growing body of literature suggested that CP-induced toxicities probably caused a result of enormous generation of reactive oxygen species (ROS) and oxidative stress that encompass severe damages to several host molecules, including lipids, proteins, and DNA, subsequently mitochondrial perturbations, and eventually apoptosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clinically applied in a various array of infections such as pneumonia as well as intra-abdominal, skin, urinary tract, and hospital-acquired infections. [5,6] Increasing evidence in preceding studies reported that CP therapy can cause renal insufficiency, [4] reproductive toxicity, [7] neurological disorder, and hepatic toxicity. [6,8] A growing body of literature suggested that CP-induced toxicities probably caused a result of enormous generation of reactive oxygen species (ROS) and oxidative stress that encompass severe damages to several host molecules, including lipids, proteins, and DNA, subsequently mitochondrial perturbations, and eventually apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…[6,8] A growing body of literature suggested that CP-induced toxicities probably caused a result of enormous generation of reactive oxygen species (ROS) and oxidative stress that encompass severe damages to several host molecules, including lipids, proteins, and DNA, subsequently mitochondrial perturbations, and eventually apoptosis. [5,9] DF is a nonsteroidal anti-inflammatory drug (NSAID) which extensively used to alleviate fever, pain, immune-mediated inflammatory reactions, and febrile conditions that are usually accompanying bacterial and viral infections. In addition, it is mostly prescribed in the management of autoimmune diseases (e.g., rheumatoid arthritis), osteoarthritis, acute sciatica, degenerative joint disease, dysmenorrhea, and postsurgical operations.…”
Section: Introductionmentioning
confidence: 99%
“…Cefpirome was initially believed to be safe for kidneys, 34 but it was established that in the older patient, administration of cefpirome could cause SCr increases. 2 Publications on cefpirome effects on kidney are very scarce. Our cefpirome study design was guided by a published study, 35 where cefpirome administered at 500 mg/ kg/d in rhesus and 800 mg/kg/d in cynomolgus resulted in severe kidney toxicity within a week of dosing in a subset of animals.…”
Section: Cefpiromementioning
confidence: 99%
“…It is marketed in several countries, and renal impairment is noted as one of the side effects. 2 Cyclosporine was introduced in the 1980s and is still widely used as an immunosuppressant in organ transplantation; however especially, prolonged use has been associated with irreversible deterioration in renal function. 3,4 Gentamicin is a widely used aminoglycoside antibiotic, with nephrotoxicity reported in approximately 10% to 25% of therapeutic courses despite careful patient monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…33 Cefepime and cefpirome were reported to be nephrotoxic but cefpirome was reported to increase the average value of serum creatinine to higher extent. 34 Cefepime-treated rats showed abnormal histopathology of liver and the kidneys. The liver showed severe dilatation and congestion on the portal vein with multiple moveable bile ductulus on portal area, certain degree of degeneration on hepatocytes occurred.…”
mentioning
confidence: 93%